Performance Evaluation of AGLETS and JADE Mobile Agent Using Encryption and Decryption Time - Dada, E. G.; Joseph, S. B.; Mishra, M. K. (ХНУРЭ, 2010)
The mobile agent approach is a relatively new concept in the distributed systems environment. The agents migrate from Client to server in a network where the state of the running program is saved, transported to the new host, and are stored, allowing the program to continue from the point where it stopped. In this paper, we evaluate the performance of the JADE and Aglet mobile agents. We developed a simulation program to evaluate the performance of the two mobile agents using the Encryption time, Decryption time and file transfer time. Our findings revealed that there is no significant difference between the performances of these two mobile agents using the parameters mentioned before.
Keywords: mobile agent; JADE; decryption; encryption